Neck circumference as a predictor of difficult intubation and difficult mask ventilation in morbidly obese patients: A prospective observational study. Issue 4 (April 2016) - Riad, Waleed; Vaez, Mercedeh N.; Raveendran, Ravi; Tam, Amanda D.; Quereshy, Fayez A.; Chung, Frances; Wong, David T.
Abstract : BACKGROUND: There is conflicting evidence as to whether obesity and neck circumference are predictors of difficult intubation in the surgical population. In addition, the cut-off neck circumference related to difficult intubation has not been clearly identified. OBJECTIVES: The primary study objective was to determine whether neck circumference and obesity were predictors of difficult intubation in morbidly obese surgical patients. Secondary outcomes included difficult mask ventilation. DESIGN: A prospective, noninterventional study. SETTING: Canadian tertiary care surgical centre between October 2012 and August 2013. PATIENTS: A total of 104 morbidly obese surgical patients (BMI ≥40 kg m −2 ) were included in the study. Eighty-eight patients were women and 16 were men. Exclusions were known difficult airway and emergency surgery. MAIN OUTCOME MEASURES: The primary outcome of the study was difficult tracheal intubation. An Intubation Difficulty Scale (IDS) was derived using seven parameters and difficult intubation was defined as IDS of at least 5. The secondary outcome was difficult mask ventilation; mask ventilation was graded as easy or difficult (inadequate, desaturation, two-handed or impossible). RESULTS: Univariate analyses showed that difficult intubation was associated with neck circumference, males, BMI more than 50 kg m −2, American Society of Anesthesiologists (ASA) status and waist circumference, and difficult mask ventilation with neck circumference, males, BMI more than 50 kg m −2 and thyromental distance. Multiple logistic regression analysis showed that neck circumference more than 42 cm ( P = 0.044) and BMI more than 50 kg m −2 ( P = 0.017) were independent predictors of difficult intubation. Male sex ( P = 0.004) and BMI more than 50 kg m −2 ( P = 0.031) were independent predictors of difficult mask ventilation.